ON THE QUESTION OF THE TEMPERATURE REGIME OF BOTTOM SEDIMENTS OF NORTHERN SEAS - Tarasov G.A.; Lyubtsov V.V.; Matishov G.G. (My University, 1988)
In this paper the results of studies of residual temperature in the profiles of bottom sediments are presented. They were conducted during 32nd and 38th expeditions on on 'Dal'nyye Zelentsy' in the Barents, Greenland, Norwegian and North Sea using techniques described by V.V. Suyetnov et al. The studies have revealed that in numerous regions, in 2-3 m vertical sections of a bottom sediment core a decrease in temperature downward is observed. Probably at some depth there is a strongly cooled horizon which retards heat flow from greater depths. The occurrence of bottom sediment cores with a tendency for temperature to decrease downward on the shelf margin and continental slope can be explained related by the discharge of interstitial water. Continental slopes and shelves are known to be the main areas of the discharge of groundwaters on the continents [15], as well as the discharge of interstitial waters as a result of compaction of sediments.